Situating the Russian Advocacy of Traditional Values in the Geopolitical Context - Gökten Doğangün (Alternatif Politika)
As epitomized by the invasion of Ukraine, the lasting geopolitical power struggle between the West and the rising nations, including Russia, has been dragging the international system towards polarization again. Its epicenter lies in the contest over the meaning of modernity that becomes particularly evident in the antagonistic attitudes towards sexual rights. Linking sexual rights to modernity has been counteracted by the discourse on traditional values. This article aims to critically examine Russia’s advocacy of traditional values in the geopolitical context. Built on the tripartite of cultural authenticity, sovereignty, and anti-Westernism, the discourse of traditional values conveys the resistance to the imposition of liberal values regarding gender equality and sexual diversity as the constitutive parameters of modernity. The investigation extends beyond a simplistic unipolar or bipolar worldview and argues that Russia’s stance is not merely counter-hegemonic against the West but also serves its imperialist aims as evidenced by its invasion of Ukraine.